Proceedings of the 2015 4th National Conference on Electrical, Electronics and Computer Engineering 2016
DOI: 10.2991/nceece-15.2016.192
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic ID-based Authenticated Group Key Agreement Protocol

Abstract: Abstract. Through the group key agreement, all group members could negotiate a common session key which is used in later secure communication. While simple GKA cannot provide enough security to resist the adversary's attack, and the malicious damage during the agreement makes the authenticated key agreement particularly important. In identity-based authentication, user's unique identity information is used as the public key, which makes it exempt from a series of management of the certification in public-key i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…It can be found from Table 2 that our protocol has the lowest computation costs, and the computation costs of our protocol and the protocol of Zheng et al [ 9 ] are very similar. However, from Figure 8 , it can be found that our protocol consumes less communication resources.…”
Section: Performance Analysis and Comparisonmentioning
confidence: 59%
See 4 more Smart Citations
“…It can be found from Table 2 that our protocol has the lowest computation costs, and the computation costs of our protocol and the protocol of Zheng et al [ 9 ] are very similar. However, from Figure 8 , it can be found that our protocol consumes less communication resources.…”
Section: Performance Analysis and Comparisonmentioning
confidence: 59%
“…There are many protocols dedicated to reducing the number of authentications between group members by reducing the number of authentication rounds. The group key agreement protocol proposed by Geng et al [ 23 ] and Zheng et al [ 9 ] divides the entire protocol into two rounds. The first round is mutual authentication between members, and the second round is group key generation.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations